"War…war never changes": exploring explicit and implicit encounters with death in a post-apocalyptic gameworld. (3rd April 2018) - Spokes, Matthew
Abstract: This paper explores how players of Fallout 4 discuss death in response to their interactions with the game and each other. Using Atkinson and Rodgers' concept of the 'murderbox', a distinction is forwarded that details player engagement in relation to explicit and implicit encounters with representations of death. Two data sources are explored using discourse analysis: the first is a player-constructed narrative charting an individual's experiences of trying to stay alive having set their own limits on survival; the second is a series of exchanges relating to the discovery of skeletons fixed in the gameworld environment. Drawing on Jenkins' work on narrative architecture, it is argued that environmental storytelling facilitates extra-narrative dialogue between players framed by reflections on the context-specific nature of mortality including the death of the avatar, emotional responses to dying at different locations in the gameworld, an interrogation of the validity of the end-of-the-world scenario and broader social death as presented in the game. In closing, the paper will argue – with regards to notions of convergence and representation – for a more nuanced consideration of mortality in videogames through both explicit and implicit encounters with death and dying.